2018
DOI: 10.1080/00207454.2017.1367295
|View full text |Cite
|
Sign up to set email alerts
|

Emergent loading dose of antiplatelets for stenting after IV rt-PA in acute ischemic stroke: a feasibility study

Abstract: Our finding preliminary suggested that an emergent loading dose of antiplatelets may be safe and feasible for acute stenting after IV rt-PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…13) Han et al also report a series of AIS patients receiving an emergent loading dose of antiplatelets (aspirin 300 mg and clopidogrel 300 mg) with acute stenting after tPA, finding a low rate of rate of hemorrhagic transformation (1/12 or 8.3%) with this protocol. 20) Our data contribute to this literature, supporting the potential safety of early antiplatelet administration after tPA in selected AIS patients.…”
Section: Discussionsupporting
confidence: 76%
“…13) Han et al also report a series of AIS patients receiving an emergent loading dose of antiplatelets (aspirin 300 mg and clopidogrel 300 mg) with acute stenting after tPA, finding a low rate of rate of hemorrhagic transformation (1/12 or 8.3%) with this protocol. 20) Our data contribute to this literature, supporting the potential safety of early antiplatelet administration after tPA in selected AIS patients.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, there have been multiple recent reports proposing the option of acute stenting on tPA with follow-up ASA/Plavix loading; however, the supporting data are greatly underpowered, with the largest series reporting on 12 patients. [3,6,24] Further investigation may establish the safety and feasibility of this option and should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The combined application of loading doses of clopidogrel and aspirin was studied in a non-thrombolytic population with cerebral infarction [17] and a bridging treatment population after thrombolysis. [18] The results showed that the loading doses of dual antiplatelet drugs could accelerate the inhibition of platelet aggregation with better therapeutic effects and no decrease in safety. These studies also lead us to propose a scientific hypothesis that, on the basis of using a lower dose of 0.6 mg/kg rt-PA to improve the safety of thrombolysis to a certain extent, administering a loaded dose of dual antiplatelet drugs may be more beneficial for improving the prognosis of Asian patients and reducing the rate of vascular re-occlusion after thrombolysis.…”
Section: Introductionmentioning
confidence: 99%